THE INFLUENCE OF ACCOUNTABILITY IN VILLAGE FUND ALLOCATION, VILLAGE POLICIES, AND VILLAGE INSTITUTIONS ON TOURISM MANAGEMENT (AN EMPIRICAL STUDY OF EDUTOURISM IN TELUK PEREPAT) - Fadila, Uci Khusnul; Mayasari, Riana; Alfiansyah, Deni Widi; Agustina, Ryna; Permata, Shakila Putri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The main objective of this study is to investigate how accountability in the Rural Capital Allocation, regulations or guidelines established at the village level, and organizations or structures within a village community influences the financial management of edutourism. The research methodology adopted is a comparative causal research approach, aiming to explore the cause-and-effect relationships among various factors. The study specifically took place at Eduwisata Teluk Perepat in Tanjung Pinang II Village, focusing on the local community as the research population. Data collection involved using a purposive sampling method, resulting in a sample size of 70 respondents. Information was gathered through a questionnaire, and subsequent analysis was carried out using multiple linear regression tests performed with SPSS version 25. The research findings reveal that accountability in the Rural Capital Allocation, regulations or guidelines established at the village level, and organizations or structures within a village community, both separately and in combination, significantly influence the financial management of Eduwisata Teluk Perepat in Tanjung Pinang Village II.